(untitled) (World Economics and Finance Bulletin, 2023)
This paper aims to assess the effects of the dynamics of US dollar exchange rates on the revenues of the Gulf oil countries, during the past fifty years (1973-2022). The researcher applied the content analysis method to evaluate publications, statistics, bulletins and reports issued by specialized institutions and experts in this field to explain the developments of US-Gulf relations, and the dynamics of dollar prices; on the oil revenues of the Gulf Cooperation Council oil countries. The researcher has reached a number of publications, reports and statistics that took place during the period from 1973 until now to explain the problems, unrest, wars and turmoil that have occurred, and their impact on the exchange rates of the dollar in the Arab Gulf states, and then the impact of this on the prices of oil and its derivatives. The research concluded that the developments of international conditions between anxiety and stability, war and peace did not change the pattern of Gulf-US relations. Hence, the movement of oil export prices was possible in the Gulf oil states; As the levels of economic and social development in the GCC countries have not weakened, despite the existence of difficult periods during the global financial crises, and perhaps the reason is the strength of the US dollar backed by a strong American economy and high liquidity in all circumstances.